2016
DOI: 10.1038/pj.2016.94
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular polymerization of hydrogen-bonded rosettes with anthracene chromophores: regioisomeric effect on nanostructures

Abstract: Two regioisomeric barbituric acid compounds possessing (phenylethynyl) anthracene cores and tridodecyloxy phenyl units were synthesized. UV-Vis spectroscopic studies showed that the two compounds self-assemble by a cooperative mechanism in methylcyclohexane (MCH) with different stacking arrangements of the π-conjugated core, which leads to distinct aggregationinduced color changes. Atomic Force Microscopic studies revealed the formation of well-defined fibrous supramolecular polymers with different topological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Seminal work by Yagai et al has shown the barbiturate unit can be employed to guide the assembly of various nanostructures such as rods, rings, coils, and catenanes. [42][43][44][45] In addition, the HB-induced arrangement of a monotopic π-conjugated system featuring a barbiturate unit was studied by STM. 46 Similar to previous work done on DAT derivatives, barbiturate systems have also been demonstrated to form HB-induced hexameric rosettes at the solid-liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal work by Yagai et al has shown the barbiturate unit can be employed to guide the assembly of various nanostructures such as rods, rings, coils, and catenanes. [42][43][44][45] In addition, the HB-induced arrangement of a monotopic π-conjugated system featuring a barbiturate unit was studied by STM. 46 Similar to previous work done on DAT derivatives, barbiturate systems have also been demonstrated to form HB-induced hexameric rosettes at the solid-liquid interface.…”
Section: Introductionmentioning
confidence: 99%